Art, Value, and Function - Schroeder, Severin (The Nordic Journal of Aesthetics, 2014)
Is the concept of a work of art an evaluative concept: does its application imply a positive evaluation? I shall discuss this question by considering two opposing attempts at defining art, namely the Institutional Theory and the view that art is a functional concept. I shall argue that the concept of art does not imply an unconditionally positive evaluation, but that art is a prestige concept. Moreover, it will be shown that functional definitions of art are flawed.